Sedimentary diterpane origins—inferences from oils of varying source depositional environment and age - Killops, S. D.; Bishop, A. N.; Tegelaar, E. W.; Urdal, K.; Ghammari, M. R. K.; Weijers, J. W. H. (Frontiers in Geochemistry, 2023)
The potential of C20 tricyclic and tetracyclic diterpane distributions in oils (and by extension, rock extracts) to aid the interpretation of sources of organic matter and depositional environmentsspanning carbonate, marl, freshwater and saline lacustrine, normal marine and transitionalfrom Neoproterozoic to Neogene, is investigated using GC-MS and GC-MS-MS analysis of a range of oils of known origin. Contributions from gymnosperms are readily distinguished by abundant characteristic tricyclics and/or tetracyclics [e.g. 5β(H)-rimuane, 5β(H)-rosane, isopimarane and phyllocladanes]. Even at low levels, phyllocladane appears a reliable indicator of Carboniferous or younger source. A fairly uniform, limited range of diterpanes at relatively low abundance is observed in oils from other sources, with the 13β(H),14α(H)-cheilanthane often being the most abundant C20 diterpane associated with carbonates and marls. Other tricyclics include the previously proposed 8βmethyl-13α-ethylpodocarpane and a series of unidentified compounds, mostly sharing mass spectra with abundant fragment ions at m/z 123, 163 and 191, together with methyl (m/z 261), but not ethyl, loss from the molecular ion. This limited range of tricyclics suggests a common group of source organisms (probably bacterial) and or diagenetic transformation resulting in a few thermodynamically stable products. It may explain why pimarane is at most a trace component, despite pimaroids being widely occurring natural products. Where gymnosperms have made little contribution, C20 tetracyclic diterpanes are typically sparse and comprise beyerane, atisanes and possibly also 16α(H)-kaurane (which co-elutes with the first of the pair of atisane isomers), with beyerane usually the most abundant in terms of m/z 276→123 response. These compounds are not detected in oils from Neoproterozoic and Cambrian carbonates, but analysis of more samples is required to confirm this trend. Despite some caveats, diterpane distributions can provide useful information related to age and depositional environment as well as providing a tool for oil-oil correlation.